Training on Handling Bodies for Takmir and The Community at The Al-Ikhlas Mosque, Gading Kulon Village, Probolinggo - Ahmad Zainullah; Hawa’ Hidayatul Hikmiyah; Ainun Zamilah; Zahida I’tisoma Billah (CENDEKIA: Jurnal Pengabdian Masyarakat, 2024)
This training was conducted due to the lack of public understanding of the procedures for handling corpses in accordance with Islamic law. This problem is often experienced by people who do not have a good religious education background. And the process of handling corpses tends to rely only on certain figures so that the process tends to be slow. This training was conducted at the Al-Ikhlas Mosque, Gading Kulon Village, Probolinggo and the participants were the caretakers and the general public. This training aims to improve understanding of handling corpses in accordance with Islamic law. And the material presented is the procedures for bathing, shrouding, praying and burying the corpse. And the impact of this training is that the caretakers and the local community gain an understanding of the procedures for handling corpses properly and in accordance with Islamic law.